Target highlights from the first post-PSI CASP experiment (CASP12, May-August 2016) - Kryshtafovych, A; Albrecht, R; Baslé, A; Bule, P; Caputo, AT; Carvalho, AL; Chao, KL; Diskin, R; Fidelis, K; Fontes, CMGA; Fredslund, F; Gilbert, HJ; et al. (Wiley, 2017)
The functional and biological significance of the selected CASP12 targets are described by the authors of the structures. The crystallographers discuss the most interesting structural features of the target proteins and assess whether these features were correctly reproduced in the predictions submitted to the CASP12 experiment.